Rubber vs. oil palm: an analysis of factors influencing smallholders' crop choice in Jambi, Indonesia - Stefan Schwarze; Michael Euler; Marcel Gatto; J. Hein; Elisabeth Hettig; Anna Mareike Holtkamp; Lutfi Izhar; Y. Kunz; J. Lay; J. Merten; S. Moser; O. Mußhoff; et al. (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
The rapid expansion of the oil palm area in many tropical countries has raised concerns about its negative impact on local communities, food security, and on the environment. While the expansion of oil palm in early stages was mainly driven by large private and public companies, it is expected that smallholders will outnumber large estates in the near future. For policy formulation it is hence important to better understand who these smallholders are and why they have started to cultivate oil palm. In this paper, we used a rich dataset collected in the province of Jambi, which is one of the most important production areas for oil palm, to analyse smallholders' decision making by combining qualitative, quantitative, and experimental methods. We identified agricultural expertise, lacking flexibility in labour requirements, availability of seedlings, and investment costs as the major constraints for farmers to cultivate oil palm. Important reasons for oil palm cultivation are the higher returns to labour and the shorter immature phase of oil palm. We also showed that oil palm farmers are neither risk-averse nor risk-loving, rather, they appear to be risk-neutral.
urn:nbn:de:gbv:7-webdoc-3954-4
Keywords: 330; smallholders; crop choice; oil palm; rubber; Indonesia